Overview of the completeness of Early Warning Score (EWS) documentation by nurses in the Emergency Installation Room (IGD) at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Muhammad Fakhri Datau; Zulkifli B. Pomalango; Dewi Hiola (Universitas Muhammadiyah Palu, 2025)
The high incidence of critical conditions and deaths due to delays in early detection is a major concern in emergency services. Although triage has been implemented at the Emergency Installation (IGD) of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City, continuous monitoring through Early Warning Score (EWS) documentation has not been carried out optimally. This study aims to find out the completeness of EWS documentation by nurses in the emergency room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. This research method is a quantitative research with an analytical descriptive design. The variable in this study is a single variable, namely the description of the completeness of EWS documentation by nurses. The sampling technique used the total sampling method with a total of 33 nurses. Data was collected through observation sheets on EWS documentation. The results of the study found that 24 respondents (72.7%) documented EWS completely, while 9 respondents (27.3%) did not complete it, especially on body temperature and urine production/hour parameters. The conclusions of this study show that although most nurses (72.7%) have implemented EWS documentation well. Suggestions are needed for routine training, supervision, and the provision of adequate facilities and infrastructure to support the completeness of EWS documentation optimally.